2020
DOI: 10.1002/hep.31418
|View full text |Cite
|
Sign up to set email alerts
|

Sirt6 Alleviated Liver Fibrosis by Deacetylating Conserved Lysine 54 on Smad2 in Hepatic Stellate Cells

Abstract: Backgrounds and Aims Activation of hepatic stellate cells (HSCs) is a central driver of fibrosis. This study aimed to elucidate the role of the deacetylase sirtuin 6 (Sirt6) in HSC activation and liver fibrosis. Approach and Results Gain‐of‐function and loss‐of‐function models were used to study the function of Sirt6 in HSC activation. Mass spectrometry was used to determine the specific acetylation site. The lecithin retinol acyltransferase–driven cyclization recombination recombinase construct (CreERT2) mous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
72
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 100 publications
(73 citation statements)
references
References 49 publications
1
72
0
Order By: Relevance
“…cRGD is pentapeptide that binds with high affinity to integrin αV and β3 which are highly expressed in a-HSC ( Li et al, 2019 ). It was also confirmed that cRGD-guided Lips specifically target activated HSC in vitro and vivo ( Li et al, 2019 ; Zhang et al, 2020 ). In agreement with a previous report, we found that RGD-Lip-delivered zileuton was highly enriched in HSC but not hepatocytes, Kupffer cells, endothelial cells or biliary cells ( Supplementary Figure S9B ).…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…cRGD is pentapeptide that binds with high affinity to integrin αV and β3 which are highly expressed in a-HSC ( Li et al, 2019 ). It was also confirmed that cRGD-guided Lips specifically target activated HSC in vitro and vivo ( Li et al, 2019 ; Zhang et al, 2020 ). In agreement with a previous report, we found that RGD-Lip-delivered zileuton was highly enriched in HSC but not hepatocytes, Kupffer cells, endothelial cells or biliary cells ( Supplementary Figure S9B ).…”
Section: Discussionmentioning
confidence: 67%
“…We used an HSC-specific drug delivery system by modifying sterically stable liposome (Lip) with cRGDyK, a pentapeptide that binds to integrin αvβ3 on the surface of a-HSC ( Li et al, 2019 ). cRGDyK-guided Lip showed high selectivity toward activated but not quiescent HSC, and preferentially accumulated in the fibrotic liver ( Li et al, 2019 ; Zhang et al, 2020 ). We loaded with zileuton, an inhibitor of 5-LO, into this delivery system (RGD-Lip/zileuton).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, SIRT6‐mediated activation of SOD2/Prdx6 pathway is pivotal for antidepressant response, which requires directing binding of SIRT6 to superoxide dismutase 2 (SOD2) and peroxiredoxin 6 (Prdx6), subsequently deacetylating them at Lys68/122 and Lys63/209, respectively 51 . Recently, SIRT6 has also been observed to suppress β–Smad family members (SMADs) 2 and 3 through deacetylation at Lys54 and Lys333/378, respectively, to protect against liver fibrosis 52,53 . Last but not least, SIRT6 was demonstrated to deacetylate p53 on K382, 54 which may significantly affect various physiological functions such as cancer prevention and stress resistance 54–57 …”
Section: Enzymatic Functionmentioning
confidence: 99%
“…Moreover, SIRT6 deacetylation may also exert liver protection by transcriptionally activating XBP1s, which confer resistance to ER stress‐induced hepatic steatosis 50 . In addition, SIRT6 activation may alleviate liver fibrosis by suppressing SMAD 2/3 signaling to affect hepatic stellate cells activation or transcriptionally inhibiting activity of orphan nuclear receptor estrogen‐related receptor γ (ERR‐γ) to impact bile acid production, representing a new therapeutic potential for treating nonalcoholic steatohepatitis (NASH) and cholestatic liver injury, respectively 52,53,261 . In terms of attenuating NASH progression, SIRT6 can also curb inflammation and oxidative stress through enhancing the nuclear import of nuclear factor Nrf2 and transcriptionally activating phase II/antioxidant genes 256 .…”
Section: Human Diseasesmentioning
confidence: 99%